Realism and international relations - Donnelly, Jack (Themes in international relations., 2000)
"Realism and International Relations provides a critical yet sympathetic survey of political realism in international theory. Using six paradigmatic theories - Hans Morgenthau, Kenneth Waltz, the Prisoners' Dilemma, Thucydides, Machiavelli, and Hobbes - the book examines realist accounts of human nature and state motivation, international anarchy, system structure and the balance of power, international institutions, and morality in foreign policy. Donnelly argues that common realist propositions not only fail to stand up to scrutiny but are rejected by many leading realists as well. Containing chapter-by-chapter guides to further reading and discussion questions for students, this book offers an accessible and lively survey of the dominant theory in International Relations."--Jacket